Binding Study of the [Ru(NH3)5pz]2+ Complex to Bile Anion Aggregates through Kinetic Measurements. Issue 12 (3rd September 2013) - Perez‐Tejeda, P.; Jimenez‐Ruiz, A.; Grueso, E. M.; Prado‐Gotor, R.; Carrasco, C.; Pastor, A.; Alvarez, N.; Garcia‐Lora, M.; Garcia‐Pageo, M.
ABSTRACT The electron transfer reaction between [Ru(NH3)5pz]2+ and [Co(C2O4)3]3− was studied in the presence of monomers and aggregates of bile salts (sodium deoxycholate, sodium taurodeoxycholate, and sodium glycocholate) at 298.2 ± 0.1 K. The results show a decreasing rate constant with the successive addition of bile salts. To rationalize the trends of the reaction rate on the [bile salts], two models were used. One of them takes into account the aggregation feature by considering a stepwise self‐association between monomers, whereas the other assumes the formation of a critical micellar concentration. Binding constants between [Ru(NH3)5pz]2+ species and deoxycholate or taurodeoxycholate aggregates were higher than that for glycocholate aggregates. These results are consistent with the way in which the monomers are added to form the bile anion aggregates.